Narcissism, Entrepreneurial Learning and Entrepreneurial Failure - Rahman, Hafiz; Amalia, Sofi (JDM (Jurnal Dinamika Manajemen), 2020)
This study evidences that psychological construct in terms of narcissistic behavior through an excessive use of social media will not boost entrepreneurs to learn from past failure experiences in business. By considering excessive narcissism through social media as a personality disorder, this study examines it as a possible cause of entrepreneurial failure. The study uses data from two sets of questionnaire with one hundred and fifty failed entrepreneurs. Analysis is quantitatively undertaken with Structural Equation Modelling/SEM and is supported by the result of Narcissistic Personality Inventory-16/NPI-16 questionnaire which reflects the degree of respondents’ narcissistic behavior. The study infers that the greater narcissistic behavior entrepreneurs has, even with the presence of entrepreneurial learning from the past failures, may lead entrepreneurs to experience subsequent failure. Stubbornness and hypocrisy are two reasons behind this. Therefore, entrepreneurs should be aware of their negative character-personality and psychological aspects when performing entrepreneurial processes.